Effects of operating practices on performance of a fixed-bed convection dryer and quality of dried longan - Marcus Nagle (2018)
Bulk layer shifting during industrial drying of whole longan was evaluated. Analysis of drying conditions and product quality of samples from different areas of the dryer was conducted. The study found that both temperature and air velocity were non-uniformly distributed during drying, which affected drying kinetics and product quality. High humidity and convective cooling of the drying air passing through the bulk caused condensation on fruits surfaces in the upper layer during the initial hours of drying. Those samples towards the sides of dryer, those initially in the upper layers, and especially those near the air inlet showed consistently lower quality. Four shifting schemes were tested, one of which was found to be exceptional in terms of end-product uniformity. Issues concerning the improvement of industrial longan drying are addressed and an optimal shifting procedure is proposed. © 2008 Institute of Food Science and Technology.